2014
DOI: 10.1007/s11745-014-3894-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Sectional Associations of Food Consumption with Plasma Fatty Acid Composition and Estimated Desaturase Activities in Finnish Children

Abstract: Plasma fatty acid (FA) composition is known to be an indicator of dietary fat quality, but the associations of other dietary factors with plasma FA composition remain unknown in children. We investigated the cross-sectional associations of food consumption with the proportions of FA and estimated desaturase activities in plasma cholesteryl esters (CE) and phospholipids (PL) among children. The subjects were a population sample of 423 children aged 6–8 years examined at baseline of The Physical Activity and Nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
4
24
1
Order By: Relevance
“…This result is in line with the recent study, reporting the lower level of oleic acid in plasma phospholipids of children fed a diet rich in fi ber [27]. In the brain tissue oleic acid is synthesized from its unsaturated precursor stearic acid (18:0), which is also synthesized by the brain or can be exogenously imported by passing the bloodbrain barrier [28].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in line with the recent study, reporting the lower level of oleic acid in plasma phospholipids of children fed a diet rich in fi ber [27]. In the brain tissue oleic acid is synthesized from its unsaturated precursor stearic acid (18:0), which is also synthesized by the brain or can be exogenously imported by passing the bloodbrain barrier [28].…”
Section: Discussionsupporting
confidence: 92%
“…We have found significantly lower serum DHA level in patients with early-stage and active JIA when compared to the control group despite a lack of differences in PUFA intake between studied groups of children, as well as intake of nutrients (dietary fiber, sugars, data not shown) which have been proven to affect plasma DHA levels in children [32]. This may suggest the impeded endogenic synthesis of DHA in active and short-lasting disease [30, 32]. This result implies a need for more information from larger, dose-response studies with meticulous dietary control, especially in young patients.…”
Section: Discussionmentioning
confidence: 85%
“…However, it has been shown that adequate dietary ALA intake may ensure ample DHA level in blood by effective conversion of ALA in liver [31]. We have found significantly lower serum DHA level in patients with early-stage and active JIA when compared to the control group despite a lack of differences in PUFA intake between studied groups of children, as well as intake of nutrients (dietary fiber, sugars, data not shown) which have been proven to affect plasma DHA levels in children [32]. This may suggest the impeded endogenic synthesis of DHA in active and short-lasting disease [30, 32].…”
Section: Discussionmentioning
confidence: 90%
“…FA composition in serum and AT was analyzed according to previously described methods ( 12,13 ). In short, the serum samples were extracted with chloroform-methanol (2:1) and the different lipid fractions, cholesteryl ester, TG, and phospholipid, were separated by solid phase extraction with an aminopropyl column.…”
Section: Assessment Of Fa Compositionmentioning
confidence: 99%